Online Learning Readiness among Junior High School Students - Tasha, Cristella; Munawar, Aqil (Jurnal Ilmiah Mandala Education (JIME), 2022)
Online learning has been helping students to access education in difficult situation, especially during the pandemic. Online learning readiness could be described through three dimensions: preference, beliefs and competence, and self-directed learning. The aim of the current study was to investigate the online learning readiness of junior-high-school students using the Online Learning Readiness Scale (OLRS). Specifically, the study examined whether there was a difference in terms of online learning readiness between eighth-grader female and male students. A sample of 116 8th graders (52 females and 64 males) from a private madrasah school in North Jakarta were used as participants in the study. The results show that most of the students were moderately ready for online learning. Based on a simple independent samples t-test, the results did not establish a statistically significant difference in online learning readiness between male students and female students. The results of the analysis showed that online learning readiness seemed to be more significantly affected by self-directed learning and computer self-efficacy, which had higher mean scores. We recommend, therefore, that online learning readiness may work well by paying attention to the intrinsic motivation of learners and access to the internet, as well as online learning tools.